Perancangan UI/UX pada Aplikasi Pencari Hotel di Karangasem - Septhiana, Kadek Wina; Rahning Putri, Luh Arida Ayu (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 3 (2025): JNATIA Vol. 3, No. 3, Mei 2025DO - 10.24843/JNATIA.2025.v03.i03.p21, 2025)
In the face of the rapidly developing digital era, hotel search applications have become an important tool for tourists to plan their trips efficiently. However, the success of a hotel search application depends not only on the accuracy of the information, but also on a satisfactory user experience. Therefore, User Interface (UI) and User Experience (UX) design plays an important role in creating attractive, functional and intuitive applications. This research discusses the design of a hotel search application in Karangasem, Bali, using the Design Thinking method. This method includes the Empathize, Define, Ideate, Prototype and Testing stages. The results showed that the application developed obtained an average score of 77.75 which represents grade B. The evaluation was carried out using the System Usability Scale (SUS) involving 10 respondents. It is hoped that this application can help tourists obtain comprehensive information about hotels in Karangasem and provide a satisfactory user experience in planning their trip.